SDO and LDO relaxation approaches to complex fractional quadratic optimization - Ashrafi, Ali; Zare, Arezu (R.A.I.R.O. Recherche opérationnelle, 2021)
This paper examines a complex fractional quadratic optimization problem subject to two quadratic constraints. The original problem is transformed into a parametric quadratic programming problem by the well-known classical Dinkelbach method. Then a semidefinite and Lagrangian dual optimization approaches are presented to solve the nonconvex parametric problem at each iteration of the bisection and generalized Newton algorithms. Finally, the numerical results demonstrate the effectiveness of the proposed approaches.